2004
DOI: 10.1103/physrevlett.92.227004
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Vortex Lattice Spinodal inNbSe2

Abstract: Metastable superheated and supercooled vortex states in NbSe2 crystals were probed with fast transport measurements over a wide range of field and temperature. The limit of metastability of the superheated vortex lattice defines a line in the phase diagram that lies below the superconducting transition and is clearly separated from it. This line is identified as the vortex lattice spinodal, and is in good agreement with recent theoretical predictions by Li and Rosenstein [Phys. Rev. B 65, 220504 (2002)]; cond-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
48
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 31 publications
7
48
0
Order By: Relevance
“…(Kato and Nagaosa, 1993). The spinodal point was observed in N bSe 2 ( Adesso et al, 2006; Thakur et al, 2005;Xiao et al, 2004) at the position consistent with the theoretical estimate.…”
Section: Spinodal Pointsupporting
confidence: 76%
“…(Kato and Nagaosa, 1993). The spinodal point was observed in N bSe 2 ( Adesso et al, 2006; Thakur et al, 2005;Xiao et al, 2004) at the position consistent with the theoretical estimate.…”
Section: Spinodal Pointsupporting
confidence: 76%
“…An independent evidence in support of the first order nature of the phase transition in typically weakly pinned single crystals of 2H-NbSe 2 came via bulk transport studies [8,9] and was confirmed via local scanning ac micro-Hall bar microscopy [10] from the visualization of an interface separating the weaker pinned (ordered) and stronger pinned (disordered) regions across the PE. The first order phase transition notion appears further fortified with the recent results of Xiao et al [11], who explored different (partially ordered) metastable states above the usually ascertained T on p . Their transport measurements essentially amount to locating higher peak temperatures (T p ) for superheated metastable states.…”
mentioning
confidence: 95%
“…[11]. In terms of the dimensionless scaled variables, LR theory gives the spinodal line as, a LR (t, h) =…”
mentioning
confidence: 99%
“…9 and 29͒ recently observed in the dynamics of several low-T c compounds. 37 The actual melting temperature ͑T m ͒ is shifted downwards due to quenched disorder and appears as a smeared spike somewhat below the theoretical value T m clean . 29 …”
Section: B Vortex Meltingmentioning
confidence: 99%